Human values in Philippine textbooks - Santos, Natividad A.
The major objective of the study was to determine the extent to which opportunities for values development are provided for in Philippine elementary school textbooks for reading instruction. The study focused on the textbook series used in public elementary schools, particularly in the Division of Quezon City. The series was developed by the Language Study Center of the Philippine Normal College and published between 1979 and 1983 by the Textbook Board of the Ministry of Education, Culture & Sports under the Elementary Education Sector Loan Agreement and Development in line with the Ten-Year Education Development Program under presidential Decree 6-A.
Keywords: Values -- Study and teaching (Elementary) -- Philippines; Reading (Elementary) -- Philippines; Textbooks -- Philippines -- Evaluation; Books and reading -- Philippines; Content area reading